Information technologies for optimization of expert systems and real-time databases - Tolstikova, O.V.; Vodopianov, S.V.; Andreiev, O.V.; Tolstikov, O.D. (Problems of Informatization and Management, 2025)
The purpose of the article is to present an integrated approach to the priorities of key performance parameters (KPIs) of the information and communication network in terms of the criteria of specificity, measurability, viability, and realistic goal setting. Planning/methodology/approach – the study was built using the Analytical Hierarchy Process (AHP) as the basis for pairwise comparisons with consideration of each KPI. Novelty – a new approach was developed aimed at step-by-step directions for making decisions for the KPI prioritization process. The results of the analysis of this problem highlight the possibility of applying the proposed approach and the calculation process for KPI prioritization. Research limitations/applicability – Rating scales in the AHP are conceptual; the research was conducted at the departments of expert systems, databases, and computer information technologies Originality/value – The article presents a new approach to KPI optimization. The proposed approach is a holistic mechanism; it will be able to provide teams with decision-making; it is also able to improve the quality of advanced technological approaches; finally, it provides broad opportunities for future research.